POLA UMUM PENGELOLAAN DAN PEMANFAATAN PUSAT SUMBER BELAJAR (PSB) DIGITAL DI SEKOLAH: Utilization of Digital Learning Resource Center (LRC) for Learning Innovation (Jurnal TEKNODIK, 2022)
This research is intended to find general patterns of management and utilization of Information and Communication Technology (ICT) -based Learning Resource Centers (LRC) in schools. There are three main questions to be answered from this research, which include; 1). What is the availability and general condition of LRC in schools? 2). How is the pattern of management and utilization of LRC in schools? 3) How is the implementation of LRC in developing ICT-based learning innovations? The research was conducted using a descriptive method by collecting data through surveys, followed by deepening the data through written testimonials. Respondents were participants of the LRC online class sympathetic.kemdikbud.go.id technical guidance which was held from February to May 2020, totaling 279 people. Recruitment of participants is open for teachers, school principals, and other education personnel at all levels of the school. The results showed: 1) in general, LRCs were already available in schools with a variety of devices and functions, but not many schools had complete LRC facilities. Meanwhile, some others already have LRC facilities but they are not sufficient. In fact, there are (20%) of the respondents who answered that there is no LRC service at their school. 2). The management of LRC in schools still varies with four main patterns, namely a. Moving equipment, b. Moving class, c. Local networked class, and d. LRC is connected to the internet. Meanwhile, the utilization of the LRC includes seven functions of the LRC in sequence; storage, service, presentation, development, training, innovation, and means of sharing. 3) Implementation in the development of learning innovations has occurred although still in a limited number. The existence of innovator teachers or driving teachers is a major factor in optimally utilizing the LRC function.
Keywords: Kata kunci; sumber belajar; konten digital; inovasi pembelajaran; pusat sumber belajar.